Ananas park: institutional cultural center through the influence of bioclimatic urbanism - Chin, Kah Meng; Ismail, Sumarni; Yusoff, Sarizal Yusman; Utaberta, Nangkula; Mohd Yunos, Mohd Yazid; Ismail, Nor Atiah (American-Eurasian Network for Scientific Information, 2015)
The urban air temperature is increasing gradually in all cities in the world. Especially tropical country where the most population living in, the heat islands effect causes the uncomfortable for the built environment. The consequences are significantly creating global temperature issues and its influences the future of the earth. As the urbanization expanding, man-made structure has replace the natural forest which the forest could protect and provide good air quality and comfortable living temperature. The concrete planning and architecture destroy the nature of environment and it also creates social issues like traffic jam in the city and overloaded of functionless space. Urbanization and architecture plays a role in contributing heat island effects. Bioclimatic urbanism is one of the effective concepts to bring back the nature into building. Climatically and contextually responses to perform a sustainable and natural living space are the main character of bioclimatic design. No doubt, the future city development has to move towards ecological design balance and the architecture serves the function being a part of urban. Several case studies have been conducting through visual survey method. The purpose of the study is to analyze the method of applying bioclimatic concept and then to propose structures that based on the concept. At the conclusion of the study, there will be a proposed recommendations that could help to reduce heat island effect and to promote healthier living condition that contribute to the public, society and the environment.